Diastereoselective Synthesis of Nitropyrrolizidines from Enantiopure exo-4-Nitro-3,5-diphenylproline through 1,3-Dipolar Cycloadditions of non-Stabilized Azomethine Ylides - Garcia-Minguens, Eduardo; Najera, Carmen; Sansano, Jose M. (Letters in Organic Chemistry, 2018)
Enantiopure exo-4-nitro-3,5-diphenylproline reacts with aldehydes and electrophilic alkenes, in good yields, through a multicomponent 1,3-dipolar cycloaddition where the intermediate azomethine ylide is generated by the decarboxylative route. The reactions with maleimides afford diastereoselectively nitropyrrolizidines. Dimethyl fumarate and 1,2-bis(phenylsulfonyl)ethylene also give variable mixtures of diastereoisomeric nitropyrrolizidines. The replacement of aldehydes by phenyl-3-buten-2- one also affords satisfactory results with high diastereoselection although in lower yields. The stereochemical outcome is studied and defined according to the absolute configuration of the resulting cycloadducts.
Keywords: azomethine ylides